A simple procedure to facilitate chin implants placement via submental approach. Issue 3 (June 2013) - Bracaglia, Roberto; Tambasco, Damiano; Gentileschi, Stefano; D'Ettorre, Marco
Abstract In order to facilitate chin implants placement by submental incision, the use of two threads is described. They are separately passed through the extremities of the implant and inserted into the previously created subperiosteal pocket using a grooved guide. Once the landmarks of dissection have been reached, the tip of the needle exits through the skin just a few centimetres laterally to the augmentation area and, only by pulling the free ends of the threads, the implant can easily be inserted into the pocket and the sutures cut and removed. This procedure was successfully performed in 79 patients of both sexes presenting with deficiencies in the sagittal dimension at the pogonion and in width, laterally to the symphysis. Therefore, in the authors' opinion, the before-described technique could be a useful tool that facial plastic surgeons can employ to facilitate alloplastic chin implants placement, by minimising the invasiveness of the procedure, reducing the operative time, and greatly improving the aesthetic result, without sacrificing the safety of the operation.